Escape from the Isle of the Lost / 4. - De la Cruz, Melissa, 1971- (Descendants, 2019)
Mal, Evie, Jay, and Carlos may have once been the baddest of the bad, but their wicked ways are (mostly) behind them-and now graduation is almost here! But before the seniors can don their custom-designed caps and gowns, courtesy of Evie, they've got an epic plan to put into action. There are tons of villain kids on the Isle of the Lost who are eager for their chance to come to Auradon Prep-even Celia, Dr. Facilier's trickster daughter, wants in on the deal!-and Mal's crew is using their upcoming visit to the Isle to help make it happen. But Auradon's biggest threat is still at large? Trapped on the other side of the barrier, Uma is more desperate than ever to get her long-awaited revenge against Mal. When she discovers an underground lair belonging to Hades, god of the underworld, Uma realizes she's found the perfect partner in crime. Together, they can defeat Mal, bring down the barrier, and escape the Isle for good.